2022
DOI: 10.5334/aogh.3564
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Factors Associated with Under-5 Mortality in Northwest Nigeria (2008–2018)

Abstract: Background:The Nigeria Demographic and Health Survey (NDHS) revealed that the underfive mortality rate (U5MR) in the northwest geopolitical zone (NWGZ), Nigeria, increased by 1.1% from 185 to 187 deaths per 1,000 live births between 2013 and 2018, indicating a setback to the previously reported modest improvement in U5MR.Objectives: This study sought to examine trends and factors related to under-5 mortality (U5M) in NWGZ from 2008 to 2018. Methods:A combined NWGZ dataset extracted from the 2008, 2013 and 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
3
2
0
Order By: Relevance
“…Compared with women who were aged 40-49 years, the child under 5 mortality rate was higher among those aged 15-19 and 20-24 years. This is consistent with findings from other countries with similar health facilities such as Nigeria [12], Bangladesh [56], and Ethiopia [57]. In PNG, adolescent girls between the ages of 15 and 19 years are frequently falling pregnant [58] putting themselves at higher risk of experiencing under-five mortality.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Compared with women who were aged 40-49 years, the child under 5 mortality rate was higher among those aged 15-19 and 20-24 years. This is consistent with findings from other countries with similar health facilities such as Nigeria [12], Bangladesh [56], and Ethiopia [57]. In PNG, adolescent girls between the ages of 15 and 19 years are frequently falling pregnant [58] putting themselves at higher risk of experiencing under-five mortality.…”
Section: Discussionsupporting
confidence: 89%
“…Biologically, these women are physically immature, vulnerable and not ready to become mothers [12]. They lack the psychological and social skills necessary to deal with pregnancy, their child's health, and parenting in general [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In study conducted with DHS data from Ghana the risk of neonatal mortality Among mothers who did not attend ANC, was approximately five times as high as the risk of neonatal deaths for mothers who attended ANC. Consistent finding was reported across the study conducted in Afghanistan, Nigeria and Ethiopia[7,25,26].…”
Section: Introductionsupporting
confidence: 88%
“…It has been observed that the male neonate had a higher likelihood of dying in the first four week of life when compared to their female counterpart. This finding was consistently found in the study conducted using DHS data in Zambia [24], Afghanistan [25], Nigeria [26], Burundi [21] and Bangladesh [27].…”
Section: Introductionsupporting
confidence: 81%